Titanium-containing composite materials

A titanium-containing composite material with a core-shell structure addresses dispersibility and transparency issues in organic solvents and resins, offering enhanced UV absorption and stability, thus improving outdoor material durability.

JP7605421B2Active Publication Date: 2024-12-24DAICEL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020202961
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-07
Publication Date
2024-12-24
Estimated Expiration
2040-12-07

AI Technical Summary

Technical Problem

Existing titanium oxide-based composite materials for organic resins suffer from poor dispersibility in organic solvents, poor transparency when blended, and inadequate ultraviolet absorption, with aromatic organic compounds facing degradation issues and titanium oxide exhibiting poor compatibility and photocatalytic activity.

Method used

A titanium-containing composite material with a specific structural unit represented by the formula [RSiO 3/2 ] and Ti-O-Si bonds, where R contains a polyoxyalkylene chain, is synthesized through a hydrolysis/condensation process using compounds (RSi(OR a ) 3 and Ti(OR b ) 4 with an acid catalyst, resulting in a core-shell structure with a polysilsesquioxane shell and titanium oxide core, enhancing dispersibility and transparency.

Benefits of technology

The composite material exhibits excellent dispersibility in organic solvents and resins, maintains transparency, and provides effective ultraviolet absorption without significant degradation, making it suitable for applications requiring UV protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605421000007
    Figure 0007605421000007
  • Figure 0007605421000008
    Figure 0007605421000008
  • Figure 0007605421000009
    Figure 0007605421000009
Patent Text Reader

Abstract

To provide a composite material excellent in dispersibility in an organic solvent, and transparency when being mixed with an organic resin, and having an ultraviolet absorption ability and hardly degrading the function.SOLUTION: A titanium-containing composite material has a constitutional unit and a TiO2 skeleton represented by following formula (1), and has Ti-O-Si bonds. [RSiO3 / 2] (1) [in the formula (1), R represents a group including a polyoxyalkylene chain]. The R is preferably a group represented by following formula (1-1). -R1-(OR2)n-OR3 (1-1) [in the formula (1-1), R1 represents a single bond or a linking group, R2 represents a 2-8C alkylene group, R3 represents a 1-4C hydrocarbon group, n represents an integral number of 2-30, and a bonding radical extending from the left of the formula bonds to a silicon atom in the formula (1)].SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to titanium-containing composite materials, and more particularly to composite materials including titanium and silicon. [Background technology]

[0002] Organic resins such as plastics gradually deteriorate when exposed to outdoor environments for long periods of time. This is mainly due to the direct effect of ultraviolet rays from sunlight breaking the bonds in the polymer with their energy, and the secondary effect of the resulting highly reactive radicals destroying the polymer in a chain reaction. For this reason, organic resin materials for outdoor use are used by coating the surface of the organic resin material with an ultraviolet absorber or by mixing it into the material.

[0003] Known UV absorbents are mainly aromatic organic compounds with UV absorbing ability and metal oxides such as titanium oxide. Aromatic organic compounds are often used in applications that require transparency because of their excellent compatibility with organic resins. However, aromatic organic compounds have a problem in that their functions are reduced due to irreversible isomerization when exposed to UV rays. On the other hand, titanium oxide has a problem in that it has a higher stability than aromatic organic compounds but has a lower compatibility with organic resins.

[0004] Methods using dispersants such as silane coupling agents and surfactants are known for the purpose of improving the compatibility between titanium oxide and organic resins. However, even when such methods are adopted, there are problems in that the compatibility with organic resins is inferior to that of aromatic organic compounds, the transparency of the dispersion composition and its molded products is inferior, and the use of crystalline (anatase type) titanium oxide makes it more likely to deteriorate the resin than deterioration caused by ultraviolet light due to its photocatalytic action.

[0005] Known examples of titanium oxide that have even better compatibility with organic resins include composite materials in which a silsesquioxane skeleton derived from aminopropyltrimethoxysilane is introduced onto the titanium oxide surface, and composite materials in which bis(trifluoromethanesulfonyl)imide is introduced (see Patent Document 1, and Non-Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2010-209288 A [Non-patent literature]

[0007] [Non-Patent Document 1] Journal of Nanoscience and Nanotechnology, (US), 2011, Vol. 11, No. 3, p. 2458-2464 [Non-Patent Document 2] Journal of Nanoscience and Nanotechnology, (US), 2020, Vol. 20, No. 5, p. 2755-2762 Summary of the Invention [Problem to be solved by the invention]

[0008] However, even the above-mentioned composite materials may have poor dispersibility in organic solvents or poor transparency when blended with organic resins.

[0009] Therefore, an object of the present disclosure is to provide a composite material that has excellent dispersibility in organic solvents and transparency when blended with an organic resin, has ultraviolet absorbing ability, and is resistant to deterioration of its function. [Means for solving the problem]

[0010] As a result of intensive research to achieve the above object, the inventors of the present disclosure have found that a specific titanium-containing composite material has excellent dispersibility in an organic solvent, excellent transparency when blended with an organic resin, and has ultraviolet absorbing ability, and its function is not easily deteriorated. The present disclosure relates to a product that has been completed based on these findings.

[0011] The present disclosure relates to a structural unit represented by the following formula (1): [RSiO 3 / 2 ] (1) [In formula (1), R is poly Rio represents a group containing an alkylene chain. and a TiO2 framework and having Ti-O-Si bonds.

[0012] The above R is represented by the following formula (1-1): -R 1 -(OR 2 ) n -OR 3 (1-1) [In formula (1-1), R 1 represents a single bond or a linking group, R 2 represents an alkylene group having 2 to 8 carbon atoms; R 3 represents a hydrocarbon group having 1 to 4 carbon atoms, n represents an integer of 2 to 30, and the bond extending from the left of the formula is bonded to the silicon atom in formula (1). It is preferable that the group is represented by the following formula:

[0013] It is preferable that when the titanium-containing composite material is dispersed in dimethyl sulfoxide, the average particle size of the dispersed particles of the composite material in dimethyl sulfoxide is 100 nm or less.

[0014] In the titanium-containing composite material, the atomic ratio of silicon atoms to titanium atoms (latter / former) is preferably 0.05 to 1.0.

[0015] The present disclosure also provides a method for producing the above-mentioned titanium-containing composite material, comprising a hydrolysis-condensation step of reacting a compound represented by the following formula (A) with a compound represented by the following formula (B) in the presence of water and an acid catalyst to hydrolyze and condense them. RSi(OR a )3(A) [In formula (A), R represents a group containing a polyoxyalkylene chain, R a represents a hydrocarbon group having 1 to 4 carbon atoms. Ti(OR b )4(B) [In formula (B), R b represents a hydrocarbon group having 1 to 6 carbon atoms.

[0016] The hydrolysis-condensation step preferably includes a condensation step in which the compound represented by the formula (A) and the compound represented by the formula (B) are reacted and condensed in the presence of the acid catalyst in a system in which no water is added, and a hydrolysis-condensation step in which water is added after the condensation step to hydrolyze and condense in the presence of water. The acid catalyst preferably contains an acidic alcohol.

[0017] The above hydrolysis and condensation step is preferably carried out by a sol-gel method. Effect of the Invention

[0018] The titanium-containing composite material of the present disclosure has excellent dispersibility in organic solvents and transparency when blended with organic resins, and has ultraviolet absorbing ability, the function of which is not easily deteriorated. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a schematic prototypical view of one embodiment of a composite material of the present disclosure. [Diagram 2] 1 is a 1H-NMR spectrum of a composite material obtained in an example. [Diagram 3] 1 shows an XRD pattern of a composite material obtained in an example. [Figure 4] 1 shows an EDX pattern of a composite material obtained in an example. [Diagram 5]1 shows UV-Vis absorption spectra of various dispersions of the composite materials obtained in the examples. [Figure 6] 1 is a DLS histogram of a DMSO dispersion of a composite material obtained in an example. [Figure 7] Photographs of five types of cast films prepared in the examples. [Figure 8] 1 shows the UV-Vis absorption spectrum of the cast film prepared in the examples. [Figure 9] 1 is a GPC curve obtained by GPC measurement of PMMA carried out in a deterioration test due to ultraviolet light. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] [Titanium-containing composite materials] The titanium-containing composite material according to one embodiment of the present disclosure has at least a constitutional unit represented by the following formula (1) and a TiO2 skeleton. The titanium-containing composite material also has a Ti-O-Si bond between the silicon atom in the formula (1) and the Ti in the TiO2 skeleton. [RSiO 3 / 2 ] (1)

[0021] The composite material preferably has a polysilsesquioxane skeleton including the constitutional unit represented by the above formula (1). The composite material also has a TiO2 skeleton.

[0022] The above composite material may include a core-shell structure having a core portion made of the above TiO2 skeleton and a shell portion made of polysilsesquioxane containing the constitutional unit represented by the above formula (1).

[0023] 1 is a schematic diagram showing a presumed example of the composite material, in which composite material 1 comprises a core portion 2 which is titanium oxide containing the TiO2 skeleton, and a shell portion 3 which is made of polysilsesquioxane containing the constitutional unit represented by formula (1) above and which is formed so as to cover core portion 2. Shell portion 3 comprises a polysilsesquioxane skeleton 31 and a polyoxyalkylene chain-containing group 32 which is present on the surface of composite material 1.

[0024] In formula (1), R represents a group containing a polyoxyalkylene chain. Examples of the polyoxyalkylene chain include a polyethylene glycol chain, a polypropylene glycol chain, a polytetramethylene glycol chain, and a polybutylene glycol chain. In the composite material, the polyoxyalkylene chain may be composed of only one type of oxyalkylene, or may be composed of two or more types of oxyalkylene. Examples of the polyoxyalkylene chain composed of two or more types of oxyalkylene include a polyethylene glycol-polypropylene glycol chain. When the polyoxyalkylene chain is composed of two or more types of oxyalkylene, the bonding form of the two or more types of oxyalkylene may be any of random, alternating, and block.

[0025] The degree of polymerization of oxyalkylene in the polyoxyalkylene chain is preferably an integer of 2 to 30, more preferably an integer of 3 to 20, still more preferably an integer of 3 to 10, and particularly preferably an integer of 3 to 5. When the degree of polymerization is 2 or more, the polyoxyalkylene chain having excellent amphiphilicity is long, and the dispersibility in water, organic solvents, and organic resins is excellent, and the transparency when blended in an organic resin is excellent. When the degree of polymerization is 30 or less, the proportion of titanium oxide structure in the composite material is relatively high, and the ultraviolet absorbing ability is excellent. In addition, the composite material can be easily synthesized.

[0026] Among them, the above R is preferably a group represented by the following formula (1-1): The bond extending from the left in the following formula (1-1) is bonded to the silicon atom in the formula (1). -R 1 -(OR 2 ) n -OR 3 (1-1)

[0027] In formula (1-1), R 1represents a single bond or a linking group (a divalent group having one or more atoms). Examples of the linking group include a divalent hydrocarbon group, a urethane bond, a carbonyl group, an ether bond, an ester bond, a carbonate bond, an amide bond, and a group in which one or more of these are linked together.

[0028] The linking group is preferably a group represented by the following formula (1-2). -R 4 -X- (1-2)

[0029] In the above formula (1-2), R 4 represents a divalent hydrocarbon group, and X represents a carbonyl group or an amide bond (preferably an amide bond). The bond extending from the left in the above formula (1-2) is bonded to the silicon atom in formula (1), and the bond extending from the right is bonded to [OR 2 ].

[0030] The above linking groups and R 4 In the above, examples of the divalent hydrocarbon group include linear or branched alkylene groups having 1 to 18 carbon atoms, and divalent alicyclic hydrocarbon groups. Examples of the linear or branched alkylene groups having 1 to 18 carbon atoms include methylene, methylmethylene, dimethylmethylene, ethylene, propylene, and trimethylene. Examples of the divalent alicyclic hydrocarbon group include cycloalkylene groups (including cycloalkylidene groups) such as 1,2-cyclopentylene, 1,3-cyclopentylene, cyclopentylidene, 1,2-cyclohexylene, 1,3-cyclohexylene, 1,4-cyclohexylene, and cyclohexylidene. The number of carbon atoms in the divalent hydrocarbon group is preferably 1 to 10, and more preferably 2 to 6.

[0031] In the above formula (1-1), R 2represents an alkylene group having 2 to 8 carbon atoms. Examples of the alkylene group having 2 to 8 carbon atoms include linear or branched alkylene groups such as methylmethylene, dimethylmethylene, ethylene, propylene, trimethylene, and tetramethylene. The number of carbon atoms in the divalent hydrocarbon group is preferably 2 to 6, and more preferably 2 to 3.

[0032] In the above formula (1-1), n ​​is an oxyalkylene group [OR 2 [ represents a degree of polymerization], and is preferably an integer of 2 to 30, more preferably an integer of 3 to 20, further preferably an integer of 3 to 10, and particularly preferably an integer of 3 to 5. When the degree of polymerization is 2 or more, the polyoxyalkylene chain having excellent amphiphilicity is long, and the dispersibility in water, organic solvents, and organic resins is excellent, and the transparency when blended in an organic resin is excellent. When the degree of polymerization is 30 or less, the proportion of the titanium oxide structure in the composite material is relatively high, and the ultraviolet absorbing ability is excellent. In addition, the synthesis of the composite material is easy.

[0033] In the above formula (1-1), R 3 represents a hydrocarbon group having 1 to 4 carbon atoms. Examples of the hydrocarbon group having 1 to 4 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, and an isobutyl group. As shown in formula (1-1), when the terminal of the polyoxyalkylene chain is R 3 By being sealed with the fluororesin, the dispersibility in organic solvents and organic resins is superior, and the transparency when blended in an organic resin is superior.

[0034] The above composite material may have only one type of constitutional unit represented by the above formula (1), or may have two or more types.

[0035] The composite material may contain other siloxane constituent units (e.g., other silsesquioxane constituent units) other than the constituent unit represented by formula (1). The siloxane constituent units refer to constituent units constituting polysiloxanes such as polysilsesquioxanes. When the other siloxane constituent units are contained, the proportion of the constituent units represented by formula (1) relative to the total amount of all siloxane constituent units in the composite material (100% by mass) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more.

[0036] The composite material has a TiO2 skeleton. That is, the composite material has a structure in which two or more oxygen atoms are bonded to a titanium atom. The coordination number of oxygen atoms to one titanium atom in the TiO2 skeleton may be 2, 3, 4, 6, or 8, and is preferably 6 from the viewpoint of excellent stability.

[0037] The atomic ratio of silicon atoms to titanium atoms (latter / former) in the composite material is preferably 0.05 to 1.0, more preferably 0.1 to 0.8, and even more preferably 0.3 to 0.6. When the atomic ratio is 0.05 or more, the proportion of titanium oxide is sufficient, and the ultraviolet absorbing ability is superior. When the atomic ratio is 1.0 or less, the dispersibility in an organic dispersion medium is superior, and the transparency when blended with an organic resin is superior. The atomic ratio can be calculated by energy dispersive X-ray (EDX) analysis.

[0038] In the above composite material, the total proportion of the polysilsesquioxane containing the structural unit represented by the above formula (1) and the TiO2 structure is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 90 mass% or more, and particularly preferably 95 mass% or more, relative to 100 mass% of the total amount of the composite material.

[0039] When the composite material is dispersed in dimethyl sulfoxide (DMSO), the average particle size of the dispersed particles of the composite material in DMSO is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 20 nm or less. When the average particle size is 100 nm or less (particularly, 50 nm or less), the dispersibility tends to be excellent when blended with an organic resin, and the transparency of the resin composition is more excellent. The average particle size is a number average particle size calculated by the cumulant method after performing dynamic light scattering (DLS) measurement at 25°C for the supernatant liquid when the composite material is mixed with DMSO at a concentration of 1 w / v% (parts by mass of the composite material relative to 100 parts by volume of DMSO).

[0040] The composite material is preferably amorphous. When the composite material is amorphous, deterioration of the resin can be further suppressed when the composite material is blended with an organic resin and used as an ultraviolet absorbent. The fact that the composite material is amorphous can be confirmed by X-ray diffraction (XRD) analysis.

[0041] The composite material has excellent dispersibility in water and organic solvents, and has excellent transparency when blended with an organic resin. This is presumably because the composite material has a structural unit in which a group containing an amphiphilic polyoxyalkylene chain is bonded to a silicon atom, and therefore has excellent dispersibility in water as well as in organic substances such as organic solvents and organic resins. In addition, the composite material contains a titanium oxide skeleton, which makes it less susceptible to isomerization and less susceptible to deterioration of ultraviolet absorption ability compared to aromatic organic compounds. In addition, the composite material is presumably more likely to become amorphous due to the inclusion of a polyoxyalkylene chain, and therefore is less likely to deteriorate the resin when blended with an organic resin.

[0042] The composite material is preferably used as an ultraviolet absorber. The composite material has excellent dispersibility in water and organic solvents and excellent transparency when blended with an organic resin, and therefore can be preferably used in a dispersion composition dispersed in a dispersion medium or a resin composition dispersed in an organic resin.

[0043] The composite material has excellent ultraviolet absorbing ability and can be used in applications where known or conventional ultraviolet absorbents are used, and can be used in, for example, cosmetics, sunscreens, inks for outdoor use, coating applications, automotive materials, sealing materials for semiconductor devices, adhesives, etc.

[0044] [Method of manufacturing titanium-containing composite materials] The above composite material can be produced, for example, through a process of reacting a compound represented by the following formula (A) with a compound represented by the following formula (B) in the presence of water and an acid catalyst to hydrolyze and condense (hydrolysis-condensation process). Only one type of compound represented by the above formula (A) and two or more types of compound represented by the above formula (B) may be used. RSi(OR a )3(A) Ti(OR b )4(B)

[0045] In the hydrolysis in the hydrolysis-condensation step, hydrolysis of the compound represented by the above formula (A) and hydrolysis of the compound represented by the above formula (B) proceed. The compound represented by the above formula (A) is a hydrolyzable compound, and is hydrolyzed to produce RSi(OH)3. Similarly, the compound represented by the above formula (B) is a hydrolyzable compound, and is hydrolyzed to produce Ti(OH)4. Next, condensation polymerization between RSi(OH)3, condensation polymerization between Ti(OH)4, and condensation between RSi(OH)3 and Ti(OH)4 proceed competitively.

[0046] The compound represented by the above formula (A) forms a structural unit represented by the above formula (1). In formula (A), R represents a group containing a polyoxyalkylene chain, and is the same as R in the above formula (1). Therefore, R is preferably a group represented by the above formula (1-1). In addition, the above formula (1-1) [-R 1 -(OR 2 ) n -OR 3 ]Middle, R 1 The linking group in the above formula (1-2) [-R 4-X-] is preferably a group represented by the formula:

[0047] Here, the compound represented by the above formula (A) may be, for example, a compound having an OR a The silane coupling agent has three R groups and a reactive functional group at the other end, and is reacted with a polyoxyalkylene monoalkyl ether to form a bond between the reactive functional group and the hydroxyl group at the polyoxyalkylene terminal. 4 and X may be derived from the structure of the silane coupling agent.

[0048] In formula (A), R a R represents a hydrocarbon group having 1 to 4 carbon atoms. Examples of the hydrocarbon group having 1 to 4 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, and an isobutyl group. a may be the same or different.

[0049] In formula (B), R b R represents a hydrocarbon group having 1 to 6 carbon atoms. Examples of the hydrocarbon group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, and a hexyl group. b Among them, a hydrocarbon group having 3 to 6 carbon atoms is preferable. When the carbon number is 3 or more, the hydrolysis rate of the compound represented by the above formula (B) becomes slow, the condensation of Ti(OH)4 molecules is delayed, and the condensation of RSi(OH)3 and Ti(OH)4 is further promoted. This makes it more difficult for the above composite material to become insoluble, and allows the above composite material to contain a sufficient amount of silicon atoms. R in the above formula (B) b may be the same or different.

[0050] Examples of the acid catalyst include mineral acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, and boric acid; phosphoric acid esters; carboxylic acids such as acetic acid, formic acid, and trifluoroacetic acid; sulfonic acids such as methanesulfonic acid, trifluoromethanesulfonic acid, and p-toluenesulfonic acid; solid acids such as activated clay; and Lewis acids such as iron chloride. In addition, an acidic alcohol such as methanolic hydrochloric acid may be used as the acid catalyst. Only one type of the acid catalyst may be used, or two or more types may be used. In addition, the acid catalyst may be used in a state of being dissolved or dispersed in water, a solvent, or the like.

[0051] In the hydrolysis and condensation step, the ratio of the compound represented by formula (A) and the compound represented by formula (B) is appropriately adjusted so that the atomic ratio of silicon atoms to titanium atoms in the composite material falls within the above-mentioned range.

[0052] The amount of the acid catalyst used is not particularly limited, and can be appropriately adjusted within the range of 0.01 to 10 moles per mole of the total amount of the compound represented by the formula (A) and the compound represented by the formula (B).

[0053] The amount of water used in the above hydrolysis and condensation step is not particularly limited, and can be appropriately adjusted within the range of 1.5 to 1000 moles per mole of the total amount of the compound represented by the above formula (A) and the compound represented by the above formula (B).

[0054] The method of adding water is not particularly limited, and the total amount of water to be used (total amount used) may be added all at once or may be added gradually. When the water is added gradually, it may be added continuously or intermittently.

[0055] The hydrolysis and condensation step can be carried out in the presence or absence of a solvent. Among them, it is preferable to carry out the step in the presence of a solvent. Examples of the solvent include aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene; ethers such as diethyl ether, dimethoxyethane, tetrahydrofuran, and 1,4-dioxane; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; esters such as methyl acetate, ethyl acetate, isopropyl acetate, and butyl acetate; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; nitriles such as acetonitrile, propionitrile, and benzonitrile; and alcohols such as methanol, ethanol, isopropyl alcohol, and butanol. Only one type of the above solvent may be used, or two or more types may be used.

[0056] The amount of the solvent used is not particularly limited, and can be appropriately adjusted within the range of 0 to 2000 parts by weight relative to 100 parts by weight of the total amount of the compound represented by the above formula (A) and the compound represented by the above formula (B) depending on the desired reaction time, etc.

[0057] The hydrolysis and condensation step is preferably carried out by a sol-gel method. By employing the sol-gel method, the reaction between the compound represented by the formula (A) and the compound represented by the formula (B) can be carried out in a homogeneous phase as a liquid phase reaction, and the reaction can be efficiently carried out at a low temperature. In the sol-gel method, for example, the reaction is started in the presence of a solvent, and the reaction is allowed to proceed while the solvent is being distilled off.

[0058] The reaction temperature in the hydrolysis and condensation step is not particularly limited, but is preferably 40 to 80°C, more preferably 50 to 60°C. The reaction time is not particularly limited, but is preferably 1.5 to 4 hours, more preferably 2 to 3 hours. The reaction in the hydrolysis and condensation step can be carried out under normal pressure, or under pressure or reduced pressure. The reaction atmosphere is not particularly limited, and may be, for example, an inert gas atmosphere such as a nitrogen atmosphere or an argon atmosphere, or in the presence of oxygen such as air. In the sol-gel method, the step of evaporating the solvent is preferably carried out in an open system. In the reaction in the hydrolysis and condensation step, the reaction temperature may be constant or may be changed during the reaction. For example, the reaction may be heated in the step of distilling off the solvent in the sol-gel method.

[0059] The hydrolysis and condensation step preferably includes a condensation step in which the compound represented by the formula (A) and the compound represented by the formula (B) are reacted and condensed under the acid catalyst in a system without adding water, and a hydrolysis and condensation step in which water is added after the condensation step to hydrolyze and condense in the presence of water. By carrying out the hydrolysis and condensation step by such a two-step reaction, the condensation step, which is the first step, suppresses the hydrolysis of the compound represented by the formula (A) and the compound represented by the formula (B), while allowing the condensation reaction of these compounds to proceed, and the hydrolysis is allowed to proceed in the second step, which is the hydrolysis and condensation step, to promote the condensation reaction. This is presumed to slow down the hydrolysis rate of the compound represented by the formula (B), and to delay the condensation of Ti(OH)4 with each other, and the titanium oxide skeleton can be surface-modified with the silsesquioxane skeleton before the titanium oxide skeleton formed aggregates, thereby obtaining a composite material that contains a large amount of titanium oxide skeleton and has excellent dispersibility in an organic solvent.

[0060] In the condensation step, the reaction is carried out in a system in which no water is added. Here, "no water is added" means that water is not intentionally added, and may include water generated in the system during the reaction.

[0061] The acid catalyst in the condensation step preferably contains an acidic alcohol. When an acidic alcohol is used, the acid catalyst can be used in a non-aqueous system, and the condensation polymerization between RSi(OH)3, the condensation polymerization between Ti(OH)4, and the condensation between RSi(OH)3 and Ti(OH)4 proceed in a well-balanced manner, thereby obtaining a titanium-containing composite with excellent dispersibility in an organic solvent.

[0062] The amount of water used in the hydrolysis and condensation step is not particularly limited, and can be appropriately adjusted within the range of 1 to 1,000 moles per mole of the total amount of the compound represented by the formula (A) and the compound represented by the formula (B).

[0063] The method of adding water is not particularly limited, and the total amount of water to be used (total amount used) may be added all at once or may be added gradually. When the water is added gradually, it may be added continuously or intermittently.

[0064] The condensation step and the hydrolysis-condensation step are preferably carried out by a sol-gel method. By adopting the sol-gel method, the reaction between the compound represented by the formula (A) and the compound represented by the formula (B) can be carried out in a homogeneous phase as a liquid phase reaction, and the reaction can be efficiently carried out at a low temperature.

[0065] The reaction temperature in the condensation step and hydrolysis-condensation step is not particularly limited, but is preferably 40 to 80°C, more preferably 50 to 60°C. The reaction time for each step is not particularly limited, but is preferably 0.1 to 10 hours, more preferably 0.5 to 5 hours. The reaction in the condensation step and hydrolysis-condensation step can be carried out under normal pressure, or under pressure or reduced pressure. The reaction atmosphere is not particularly limited, and may be, for example, an inert gas atmosphere such as a nitrogen atmosphere or an argon atmosphere, or in the presence of oxygen such as air. In the sol-gel method, the step of distilling off the solvent is preferably carried out in an open system. In the reaction in the condensation step and hydrolysis-condensation step, the reaction temperature may be constant or may be changed during the reaction. For example, the reaction may be heated in the step of distilling off water in the sol-gel method.

[0066] After completion of the hydrolysis and condensation step, the product may be separated and purified by a separation means such as water washing, acid washing, alkali washing, filtration, concentration, distillation, extraction, reprecipitation, column chromatography, or a combination of these separation means.

[0067] [Dispersion composition] The composite material has excellent dispersibility in water and organic solvents. Therefore, the composite material can be used to obtain a dispersion composition containing a dispersion medium and the composite material dispersed in the dispersion medium. In the dispersion composition, only one type of the composite material may be used, or two or more types of the composite material may be used.

[0068] Examples of the dispersion medium include water, aqueous solutions, and organic solvents. Examples of the organic solvent include aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene; ethers such as diethyl ether, dimethoxyethane, tetrahydrofuran, and 1,4-dioxane; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; esters such as methyl acetate, ethyl acetate, isopropyl acetate, and butyl acetate; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; nitriles such as acetonitrile, propionitrile, and benzonitrile; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, pentanol, and hexanol; halogenated hydrocarbons such as dichloromethane and chloroform; and sulfoxides such as dimethyl sulfoxide. The dispersion medium may be one type or a mixture of two or more types.

[0069] As the dispersion medium, from the viewpoint of excellent dispersibility of the composite material, water, aromatic hydrocarbons, ethers, ketones, amides, nitriles, alcohols, and halogenated hydrocarbons are particularly preferred.

[0070] The ratio of the composite material dispersed in the dispersion composition is preferably 0.1 to 10 parts by mass (w / v%), more preferably 0.5 to 1 part by mass (w / v%), relative to 100 parts by volume of the total amount of the dispersion medium. The dispersion composition has excellent dispersibility of the composite material, so that an amount within the above range can be dispersed.

[0071] The dispersion composition may be composed of only the composite material and the dispersion medium, or may contain other components. Examples of other components include dispersants, surfactants, thickeners, coupling agents, rust inhibitors, corrosion inhibitors, freezing point depressants, antifoaming agents, anti-wear additives, preservatives, and colorants. Since the composite material has excellent dispersibility in the dispersion medium even without using a dispersant, the content ratio of the dispersant, surfactant, and coupling agent in the dispersion composition is preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably less than 1% by mass, based on the total amount of the dispersion composition (100% by mass).

[0072] The average particle size of the composite dispersed particles in the dispersion composition is preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 20 nm or less. If the average particle size is 100 nm or less (particularly 50 nm or less), the dispersibility tends to be excellent when blended with an organic resin, and the transparency of the resin composition is more excellent. The average particle size is a number average particle size calculated by the cumulant method at a composite concentration of 1 w / v% by dynamic light scattering (DLS) measurement at 25°C.

[0073] The above dispersion composition has a haze value of preferably 5 or less, more preferably 3 or less, even more preferably 1 or less, even more preferably 0.5 or less, even more preferably 0.1 or less, and particularly preferably 0.05 or less. The above dispersion composition has excellent dispersibility of the composite material, so that a dispersion composition with the above haze value can be obtained. The above haze value can be measured based on JIS K7136.

[0074] [Resin composition] The composite material has excellent dispersibility in an organic resin. Therefore, the composite material can be used to obtain a resin composition containing a resin matrix and the composite material dispersed in the resin matrix. In the dispersion composition, only one type of the composite material may be used, or two or more types of the composite material may be used.

[0075] Examples of the resin constituting the resin matrix include thermoplastic resins and thermosetting resins.

[0076] Examples of the thermoplastic resin include polystyrene resins, vinyl acetate resins, polyester resins, polyolefin resins (e.g., polyethylene resins, polypropylene resin compositions, etc.), polyimide resins, acrylic resins such as polymethyl methacrylate (PMMA), polycarbonates, polyimides, polyglycerin, polyacetals, etc. The thermoplastic resins may be used alone or in combination of two or more.

[0077] Examples of the thermosetting resin include phenolic resins, epoxy resins, oxetane resins, urethane resins, melamine resins, alkyd resins, silicone resins, unsaturated polyester resins, urea resins, etc. Only one type of the thermosetting resin may be used, or two or more types may be used.

[0078] The resin composition may contain various additives in addition to the above-mentioned components. Examples of the additives include dispersants, surfactants, thickeners, coupling agents, rust inhibitors, corrosion inhibitors, freezing point depressants, defoamers, anti-wear additives, preservatives, colorants, flame retardants, leveling agents, ion adsorbents, ultraviolet absorbers other than the composite material, light stabilizers, fluorescent brighteners, and fillers. The content of the additives is not particularly limited and can be appropriately selected. Since the composite material has excellent dispersibility in organic resins even without using a dispersant, the content ratio of the dispersant, surfactant, and coupling agent in the resin composition is preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably less than 1% by mass, based on the total amount of the resin composition (100% by mass).

[0079] The composite material has excellent transparency even when molded only from the composite material. Therefore, the content of the composite material in the resin composition is not particularly limited from the viewpoint of transparency, and is appropriately adjusted so that the resin composition has the desired characteristics. The content of the composite material in the resin composition is, for example, 30 to 300 parts by mass, preferably 50 to 200 parts by mass, relative to 100 parts by mass of the total amount of the resins constituting the resin matrix.

[0080] The resin composition may be prepared by mixing and dispersing the composite material in an organic resin, or by curing a curable composition in which the composite material is dispersed in a curable compound (polymerizable compound) that is cured by polymerization to form a resin.

[0081] [Curable composition] Examples of the curable compound include cationic curable compounds, radical curable compounds, and anionic curable compounds. Examples of the cationic curable compound include compounds having an epoxy group (epoxy compounds), compounds having an oxetanyl group (oxetane compounds), and compounds having a vinyl ether group (vinyl ether compounds). Among them, epoxy compounds are preferred because the composite material has poor reactivity with epoxy groups and the stability of the curable composition is excellent. The curable compounds may be used alone or in combination.

[0082] As the epoxy compound, any known or commonly used compound having one or more epoxy groups (oxirane rings) in the molecule can be used, and although there is no particular limitation, examples thereof include alicyclic epoxy compounds (alicyclic epoxy resins), aromatic epoxy compounds (aromatic epoxy resins), aliphatic epoxy compounds (aliphatic epoxy resins), and the like.

[0083] The alicyclic epoxy compound includes known or conventional compounds having one or more alicyclic rings and one or more epoxy groups in the molecule, and is not particularly limited. For example, the compound includes (1) a compound having an epoxy group (referred to as an "alicyclic epoxy group") composed of two adjacent carbon atoms and an oxygen atom constituting an alicyclic ring in the molecule; (2) a compound in which an epoxy group is directly bonded to an alicyclic ring by a single bond; and (3) a compound having an alicyclic ring and a glycidyl ether group in the molecule (glycidyl ether type epoxy compound).

[0084] The above (1) compound having an alicyclic epoxy group in the molecule includes a compound represented by the following formula (i). [ka]

[0085] In the above formula (i), Y represents a single bond or a linking group (a divalent group having one or more atoms). Examples of the linking group include a divalent hydrocarbon group, an alkenylene group in which a part or all of the carbon-carbon double bonds are epoxidized, a carbonyl group, an ether bond, an ester bond, a carbonate group, an amide group, and a group in which a plurality of these are linked together. In addition, a substituent such as an alkyl group may be bonded to one or more of the carbon atoms constituting the cyclohexane ring (cyclohexene oxide group) in formula (i).

[0086] Examples of the divalent hydrocarbon group include linear or branched alkylene groups having 1 to 18 carbon atoms, and divalent alicyclic hydrocarbon groups. Examples of the linear or branched alkylene groups having 1 to 18 carbon atoms include methylene, methylmethylene, dimethylmethylene, ethylene, propylene, and trimethylene. Examples of the divalent alicyclic hydrocarbon group include divalent cycloalkylene groups (including cycloalkylidene groups) such as 1,2-cyclopentylene, 1,3-cyclopentylene, cyclopentylidene, 1,2-cyclohexylene, 1,3-cyclohexylene, 1,4-cyclohexylene, and cyclohexylidene.

[0087] Examples of the alkenylene group in the alkenylene group in which some or all of the carbon-carbon double bonds have been epoxidized (sometimes referred to as "epoxidized alkenylene group") include linear or branched alkenylene groups having 2 to 8 carbon atoms, such as vinylene group, propenylene group, 1-butenylene group, 2-butenylene group, butadienylene group, pentenylene group, hexenylene group, heptenylene group, and octenylene group. In particular, the epoxidized alkenylene group is preferably an alkenylene group in which all of the carbon-carbon double bonds have been epoxidized, and more preferably an alkenylene group having 2 to 4 carbon atoms in which all of the carbon-carbon double bonds have been epoxidized.

[0088] Representative examples of the alicyclic epoxy compound represented by the above formula (i) include (3,4,3',4'-diepoxy)bicyclohexyl and compounds represented by the following formulas (i-1) to (i-10). In the following formulas (i-5) and (i-7), l and m each represent an integer of 1 to 30. In the following formula (i-5), R' is an alkylene group having 1 to 8 carbon atoms, and among these, a linear or branched alkylene group having 1 to 3 carbon atoms, such as a methylene group, an ethylene group, a propylene group, or an isopropylene group, is preferred. In the following formulas (i-9) and (i-10), n1 to n6 each represent an integer of 1 to 30. Other examples of the alicyclic epoxy compound represented by the above formula (i) include 2,2-bis(3,4-epoxycyclohexyl)propane, 1,2-bis(3,4-epoxycyclohexan-1-yl)ethane, 1,2-epoxy-1,2-bis(3,4-epoxycyclohexan-1-yl)ethane, and bis(3,4-epoxycyclohexylmethyl)ether. [ka] [ka]

[0089] Examples of the above-mentioned (2) compound in which an epoxy group is directly bonded to an alicyclic ring via a single bond include a compound represented by the following formula (ii). [ka]

[0090] In formula (ii), R" is a group (p-valent organic group) obtained by removing p hydroxyl groups (-OH) from the structural formula of a p-valent alcohol, and p and n each represent a natural number. p Examples of the compound represented by the formula (ii) include polyhydric alcohols (alcohols having 1 to 15 carbon atoms) such as 2,2-bis(hydroxymethyl)-1-butanol. p is preferably 1 to 6, and n is preferably 1 to 30. When p is 2 or more, n in each group in ( ) (in the outer parentheses) may be the same or different. Specific examples of the compound represented by the formula (ii) include 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol [for example, trade name "EHPE3150" (manufactured by Daicel Corporation)].

[0091] Examples of the above-mentioned (3) compound having an alicyclic ring and a glycidyl ether group in the molecule include, for example, glycidyl ether of alicyclic alcohol (particularly, alicyclic polyhydric alcohol). More specifically, for example, compounds obtained by hydrogenating bisphenol A type epoxy compounds such as 2,2-bis[4-(2,3-epoxypropoxy)cyclohexyl]propane and 2,2-bis[3,5-dimethyl-4-(2,3-epoxypropoxy)cyclohexyl]propane (hydrogenated bisphenol A type epoxy compounds); bis[o,o-(2,3-epoxypropoxy)cyclohexyl]methane, bis[o,p-(2,3-epoxypropoxy)cyclohexyl]methane, bis[p,p-(2,3-epoxypropoxy)cyclohexyl]methane, bis[3,5-dimethyl Examples of such epoxy compounds include hydrogenated compounds of bisphenol F type epoxy compounds such as [3-(2,3-epoxypropoxy)cyclohexyl]methane (hydrogenated bisphenol F type epoxy compounds); hydrogenated biphenol type epoxy compounds; hydrogenated phenol novolac type epoxy compounds; hydrogenated cresol novolac type epoxy compounds; hydrogenated cresol novolac type epoxy compounds of bisphenol A; hydrogenated naphthalene type epoxy compounds; hydrogenated epoxy compounds of epoxy compounds obtained from trisphenolmethane; and hydrogenated epoxy compounds of the aromatic epoxy compounds listed below.

[0092] Examples of the aromatic epoxy compounds include epi-bis-type glycidyl ether epoxy resins obtained by a condensation reaction between bisphenols [e.g., bisphenol A, bisphenol F, bisphenol S, fluorene bisphenol, etc.] and epihalohydrin; high molecular weight epi-bis-type glycidyl ether epoxy resins obtained by further addition reaction of these epi-bis-type glycidyl ether epoxy resins with the above-mentioned bisphenols; phenols [e.g., phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F], and the like. Novolak alkyl type glycidyl ether epoxy resins are obtained by condensing polyhydric alcohols obtained by the condensation reaction of polyphenols (e.g., bisphenol S) with aldehydes (e.g., formaldehyde, acetaldehyde, benzaldehyde, hydroxybenzaldehyde, salicylaldehyde) with epihalohydrin; and epoxy compounds in which two phenol skeletons are bonded to the 9-position of the fluorene ring and a glycidyl group is bonded directly or via an alkyleneoxy group to the oxygen atom obtained by removing the hydrogen atom from the hydroxyl group of each of the phenol skeletons.

[0093] Examples of the aliphatic epoxy compounds include glycidyl ethers of q-valent alcohols (where q is a natural number) that do not have a cyclic structure; glycidyl esters of mono- or polyvalent carboxylic acids (e.g., acetic acid, propionic acid, butyric acid, stearic acid, adipic acid, sebacic acid, maleic acid, itaconic acid, etc.); epoxidized products of oils and fats having double bonds, such as epoxidized linseed oil, epoxidized soybean oil, and epoxidized castor oil; and epoxidized products of polyolefins (including polyalkadienes), such as epoxidized polybutadiene. Examples of the q-valent alcohols not having a cyclic structure include monohydric alcohols such as methanol, ethanol, 1-propyl alcohol, isopropyl alcohol, and 1-butanol; dihydric alcohols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, polyethylene glycol, and polypropylene glycol; and trihydric or higher polyhydric alcohols such as glycerin, diglycerin, erythritol, trimethylolethane, trimethylolpropane, pentaerythritol, dipentaerythritol, and sorbitol. The q-valent alcohol may be polyether polyol, polyester polyol, polycarbonate polyol, polyolefin polyol, or the like.

[0094] The oxetane compound includes known or commonly used compounds having one or more oxetane rings in the molecule, and is not particularly limited. For example, 3,3-bis(vinyloxymethyl)oxetane, 3-ethyl-3-(hydroxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-[(phenoxy)methyl]oxetane, 3-ethyl-3-(hexyloxymethyl)oxetane, 3-ethyl-3-(chloromethyl)oxetane, 3,3-bis(chloromethyl)oxetane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, bis{[1 -ethyl(3-oxetanyl)]methyl} ether, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]bicyclohexyl, 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]cyclohexane, 1,4-bis{[(3-ethyl-3-oxetanyl)methoxy]methyl}benzene, 3-ethyl-3-{[(3-ethyloxetan-3-yl)methoxy]methyl)}oxetane, xylylene bisoxetane, 3-ethyl-3-{[3-(triethoxysilyl)propoxy]methyl}oxetane, oxetanyl silsesquioxane, and phenol novolak oxetane.

[0095] As the vinyl ether compound, known or conventional compounds having one or more vinyl ether groups in the molecule can be used, and are not particularly limited. Examples of the vinyl ether compound include 2-hydroxyethyl vinyl ether (ethylene glycol monovinyl ether), 3-hydroxypropyl vinyl ether, 2-hydroxypropyl vinyl ether, 2-hydroxyisopropyl vinyl ether, 4-hydroxybutyl vinyl ether, 3-hydroxybutyl vinyl ether, 2-hydroxybutyl vinyl ether, 3-hydroxyisobutyl vinyl ether, 2-hydroxyisobutyl vinyl ether, 1-methyl-3-hydroxypropyl vinyl ether, 1-methyl-2-hydroxypropyl vinyl ether, 1-hydroxymethylpropyl vinyl ether, 4-hydroxycyclohexyl vinyl ether, 1,6-hexanediol monovinyl ether, 1,6-hexanediol divinyl ether, 1,8-octanediol divinyl ether, 1,4-cyclohexanedimethanol monovinyl ether, 1,4-cyclohexanedimethanol divinyl ether, 1,3-cyclohexanedimethanol monovinyl ether, 1,3-cyclohexanedimethanol divinyl ether, 1,2-cyclohexanedimethanol monovinyl ether, 1,2-Cyclohexanedimethanol divinyl ether, p-xylene glycol monovinyl ether, p-xylene glycol divinyl ether, m-xylene glycol monovinyl ether, m-xylene glycol divinyl ether, o-xylene glycol monovinyl ether, o-xylene glycol divinyl ether, ethylene glycol divinyl ether, diethylene glycol monovinyl ether, diethylene glycol divinyl ether, triethylene glycol monovinyl ether, triethylene glycol divinyl ether, tetraethylene glycol monovinyl ether, tetraethylene glycol divinyl ether, pentaethylene glycol monovinyl ether, pentaethylene glycol divinyl ether, oligoethylene glycol monovinyl ether, oligoethylene glycol divinyl ether, polyethylene glycol monovinyl ether, polyethylene glycol divinyl ether, dipropylene glycol monovinyl ether, dipropylene glycol divinyl ether, tripropylene glycol monovinyl ether novinyl ether, tripropylene glycol divinyl ether, tetrapropylene glycol monovinyl ether, tetrapropylene glycol divinyl ether, pentapropylene glycol monovinyl ether, pentapropylene glycol divinyl ether, oligopropylene glycol monovinyl ether, oligopropylene glycol divinyl ether, polypropylene glycol monovinyl ether, polypropylene glycol divinyl ether, isosorbide divinyl ether, oxanorbornane divinyl ether, phenyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, octyl vinyl ether, cyclohexyl vinyl ether, hydroquinone divinyl ether, 1,4-butanediol divinyl ether, cyclohexane dimethanol divinyl ether, trimethylolpropane divinyl ether, trimethylolpropane trivinyl ether, bisphenol A divinyl ether, bisphenol F divinyl ether, hydroxyoxanorbornane methanol divinyl ether, 1,Examples of the vinyl vinyl ether include 4-cyclohexanediol divinyl ether, pentaerythritol trivinyl ether, pentaerythritol tetravinyl ether, dipentaerythritol pentavinyl ether, and dipentaerythritol hexavinyl ether.

[0096] The curable composition may contain, together with the curable compound, a curing agent, a curing accelerator, a curing catalyst, etc., depending on the polymerization form of the curable compound. Only one of these may be used, or two or more of them may be used.

[0097] When the curable compound is an epoxy compound, examples of the curing agent include acid anhydrides, amines, polyamide resins, imidazoles, polymercaptans, phenols, polycarboxylic acids, dicyandiamides, and organic acid hydrazides.

[0098] The curing accelerator is a compound that is used together with the curing agent and has the function of accelerating the reaction rate when the epoxy compound reacts with the curing agent. Examples of the curing accelerator include 1,8-diazabicyclo[5.4.0]undecene-7 (DBU) or a salt thereof (e.g., phenol salt, octylate salt, p-toluenesulfonate salt, formate salt, tetraphenylborate salt, etc.); 1,5-diazabicyclo[4.3.0]nonene-5 (DBN) or a salt thereof (e.g., phenol salt, octylate salt, p-toluenesulfonate salt, formate salt, tetraphenylborate salt, etc.); tertiary amines such as benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and N,N-dimethylcyclohexylamine; imidazoles such as 2-ethyl-4-methylimidazole and 1-cyanoethyl-2-ethyl-4-methylimidazole; phosphines such as phosphoric acid esters and triphenylphosphine; phosphonium compounds such as tetraphenylphosphonium tetra(p-tolyl)borate; organic metal salts such as zinc octylate and tin octylate; and metal chelates.

[0099] When the curable compound is an epoxy compound, the curing catalyst is not particularly limited, but examples thereof include cationic polymerization initiators (photocationic polymerization initiators, thermal cationic polymerization initiators, etc.) that generate cationic species by applying light irradiation, heat treatment, etc., and initiate polymerization, Lewis acid-amine complexes, Bronsted acid salts, and imidazoles.

[0100] The curable composition may contain additives in addition to the above-mentioned components. When the additive contains a compound having a hydroxyl group such as ethylene glycol, diethylene glycol, propylene glycol, or glycerin (particularly, an aliphatic polyhydric alcohol), the reaction can proceed slowly. Other examples include solvents and additives that may be contained in the resin composition. The content of the additives is not particularly limited and can be appropriately selected. Since the composite material has excellent dispersibility in the curable composition even without using a dispersant, the content ratio of the dispersant, surfactant, and coupling agent in the curable composition is preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably less than 1% by mass, relative to the total amount of the curable composition (100% by mass).

[0101] Each aspect disclosed in this specification can be combined with any other feature disclosed in this specification. Each configuration in each embodiment and their combinations are merely examples, and addition, omission, substitution, and other modifications of the configuration are possible as appropriate within the scope of the present disclosure. In addition, each invention according to this disclosure is not limited by the embodiments or the following examples, but is limited only by the claims. EXAMPLES

[0102] Hereinafter, one embodiment of the present disclosure will be described in more detail based on examples.

[0103] Synthesis Example 1 0.5027g (3.0mmol) of triethylene glycol monomethyl ether (purity: 98%) was added to 0.5208g (2.0mmol) of 3-(triethoxysilyl)propyl isocyanate (purity: 95%), and 0.0472g (0.04mmol) of triethylenediamine (purity: 95%) was used as a catalyst. The mixture was stirred in 1,4-dioxane at about 80°C for 2 hours to synthesize a compound represented by the following formula (A-1). Note that since there was no difference in solubility between the compound represented by the above formula (A-1) and triethylene glycol monomethyl ether, separation was difficult, and there was a risk that the sol-gel reaction would proceed by distilling off the solvent. Therefore, the compound represented by the above formula (A-1) and triethylene glycol monomethyl ether were used in the subsequent reaction as a 1,4-dioxane solution containing the compound represented by the above formula (A-1) and triethylene glycol monomethyl ether without purification. [ka]

[0104] Example 1 The titanium-containing composite material was synthesized by a two-stage sol-gel reaction. First, in the first stage reaction, 0.2992 g (1.0 mmol) of titanium tetraisopropoxide (purity: 95%) and 3.0 mL of methanolic hydrochloric acid (0.5 mol / L) were added to the 1,4-dioxane solution obtained in Synthesis Example 1, and the mixture was stirred at room temperature for 2 hours. The mixture was then heated to about 50°C in an open system, and the solvent was distilled off over about 2 hours to carry out the reaction, resulting in a viscous product. In the second stage reaction, in order to further promote the condensation reaction, about 20 mL of water was added to the product, and the mixture was heated again to about 50°C in an open system, and the reaction was carried out by stirring while distilling off the water over about 2 hours. About 20 mL of acetone was added to the obtained crude product, and the soluble portion was collected by suction filtration. The acetone-soluble portion was concentrated to about 3 mL by a rotary evaporator, and the viscous product obtained by reprecipitation by pouring into about 100 mL of hexane was isolated by decantation. Finally, the above product was dissolved in approximately 20 mL of acetone, and the solution was transferred to a sample bottle (volume 50 mL). The solvent was then removed using a rotary evaporator, and the solution was then dried by heating at 100°C under normal pressure for approximately 1 hour to obtain a titanium-containing composite material (yield: 0.4604 g). The theoretical yield of titanium-containing composite material from the above reaction is 0.6807 g (= TiO2 (FW = 79.87): 1.0 mmol (0.0799 g) + SiO 3 / 2 (CH2)3NH(C=O)OCH2CH2(OCH2CH2)2OCH3 (FW=300.39):2.0 mmol (0.6008 g)), and the yield was calculated by dividing the actual yield by the theoretical yield, 68% (=0.4604 / 0.6807×100).

[0105] The FT-IR data of the titanium-containing composite material obtained in Example 1 is shown below. IR (KBr, cm -1 ), 1704cm -1 (C=O of urethane group),1538cm -1 (NH of urethane group) Obtained in Example 1 1The peak data for the H-NMR spectrum (400 MHz, DO) are shown below. δ 4.26-4.13(br,2H,-NH(C=O)OCH2CH2(OCH2CH2)2OCH3) δ 3.78-3.54(br,10H,-NH(C=O)OCH2CH2(OCH2CH2)2OCH3) δ 3.40-3.33(br,3H,-NH(C=O)OCH2CH2(OCH2CH2)2OCH3) δ 3.20-3.03(br,2H,-SiCH2CH2CH2NH(C=O)O-) δ 1.59-1.49(br,2H,-SiCH2CH2CH2NH(C=O)O-) δ 0.60-0.53(br,2H,-SiCH2CH2CH2NH(C=O)O-)

[0106] the above 1 From the 1 H-NMR spectrum, a signal derived from a triethylene glycol monomethyl ether chain was observed, confirming that the composite material of Example 1 contained a polysilsesquioxane component.

[0107] Example 2 The titanium-containing composite material was synthesized by a one-step sol-gel reaction. 0.2992 g (1.0 mmol) of titanium tetraisopropoxide (purity: 95%) and 3.0 mL of hydrochloric acid aqueous solution (1.0 mol / L) were added to the 1,4-dioxane solution obtained in Synthesis Example 1, and the mixture was stirred at room temperature for 2 hours. The mixture was then heated to about 50°C in an open system, and the solvent was distilled off over about 2 hours to carry out the reaction. The mixture was then dried in an oven at 100°C for 2 hours to obtain a crude product. About 20 mL of acetone was added to the obtained crude product, and the soluble portion was collected by suction filtration. The acetone-soluble portion was concentrated to about 3 mL using a rotary evaporator, and the viscous product obtained by reprecipitation by pouring it into about 100 mL of hexane was isolated by decantation. Finally, the above product was dissolved in approximately 20 mL of acetone, and the solution was transferred to a sample bottle (volume 50 mL). The solvent was then removed using a rotary evaporator, and the solution was then dried by heating at 100°C under normal pressure for approximately 1 hour to obtain a titanium-containing composite material (yield: 0.4267 g). The theoretical yield of the titanium-containing composite material from the above reaction was 0.6807 g, and the yield was calculated by dividing the actual yield by the theoretical yield, ie, 63% (=0.4267 / 0.6807×100).

[0108] The FT-IR data of the titanium-containing composite material obtained in Example 2 is shown below. IR (KBr, cm -1 ), 1704cm -1 (C=O of urethane group),1538cm -1 (NH of urethane group) Obtained in Example 1 1 The peak data for the H-NMR spectrum (400 MHz, DO) are shown below. δ 4.26-4.12(br,2H,-NH(C=O)OCH2CH2(OCH2CH2)2OCH3) δ 3.79-3.53(br,10H,-NH(C=O)OCH2CH2(OCH2CH2)2OCH3) δ 3.40-3.29(br,3H,-NH(C=O)OCH2CH2(OCH2CH2)2OCH3) δ 3.20 - 3.02 (br, 2H, -SiCH2CH2CH2NH(C=O)O-) δ 1.69 - 1.51 (br, 2H, -SiCH2CH2CH2NH(C=O)O-) δ 0.78 - 0.56 (br, 2H, -SiCH2CH2CH2NH(C=O)O-)

[0109] The above 1 From the H-NMR spectrum, signals derived from the triethylene glycol monomethyl ether chain were observed, confirming that the composite material of Example 2 contains a polysilsesquioxane component.

[0110] FT-IR measurements and 1 The conditions for H-NMR measurements of each composite material obtained in Examples 1 and 2 are as follows. Also, the following evaluations were performed on each composite material obtained in Examples 1 and 2.

[0111] <FT-IR Measurement> Performed using a Fourier transform infrared spectrophotometer "FT / IR-4200 type A" (manufactured by JASCO Corporation).

[0112] < 1 <H-NMR Measurement> A measurement sample was prepared by dissolving a composite material (about half a spatula cup) and a small amount of sodium 3-trimethylsilyl-1-propanesulfonate in 0.6 mL of D2O. The nuclide was 1 proton, the sequence was set to single_pulse.ex2, and the measurement was performed with 8 accumulations. The H-NMR spectra of the composite materials of Examples 1 and 2 1 are shown in Figures 2(a) and (b), respectively.

[0113] <XRD Measurement> XRD measurements were performed on each of the composite materials obtained in Examples 1 and 2. 0.0134 g of the above composite material was mixed and dissolved in about 1 mL of methanol, applied onto a glass substrate, and dried at room temperature to prepare a cast film. Then, XRD measurement was performed on the obtained cast film. As the X-ray source, Cu Kα ray (0.15418 nm) filtered with Ni was used. As the measuring apparatus, “X’Pert Pro diffractometer” manufactured by Malvern Panalytical was used. The XRD patterns of the composite materials of Examples 1 and 2 are shown in FIGS. 3(a) and (b), respectively. No peak derived from crystallinity was confirmed in the XRD pattern, and it was confirmed that the composite materials of Examples 1 and 2 are amorphous.

[0114] <EDX Measurement> EDX measurements were performed on each of the composite materials obtained in the examples. The measurement sample was prepared by attaching the above composite material to a carbon tape. The composite material that was not sufficiently attached to the carbon tape was removed using a blower. No vapor deposition treatment was performed. The measurement was performed in the low vacuum mode. As the measuring apparatus, “XL30CP” manufactured by FEI Company, Ltd., Japan was used. The EDX patterns of the composite materials of Examples 1 and 2 are shown in FIGS. 4(a) and (b), respectively. The atomic ratio (the former / latter) of titanium atoms to silicon atoms in the composite material was 0.45 in Example 1, which was almost the same as the charging ratio. In Example 2, it was 0.18.

[0115] <Dispersibility in Organic Solvents> For each of the composite materials obtained in Examples 1 and 2, evaluation of dispersibility with respect to each of the solvents shown in the table was performed. At room temperature, the composite material was mixed to be 1 part by mass with respect to 100 parts by volume of the solvent (1 w / v%), and stirred to prepare a mixed solution. Then, each mixed solution was visually observed, and the dispersibility was evaluated according to the following criteria. The results are shown in Table 1. +: No particles were visually confirmed, and it was judged that the dispersibility was good ±: Some particles were visually confirmed, and it was judged that it was partially dispersed -: The amount of particles that could be visually confirmed was about the same as the input amount, and it was judged that it was not dispersed

Table 1

[0116] <UV-Vis Absorption Spectrum Measurement> 0.0200 g of each composite material obtained in Examples 1 and 2 was added to 2 mL of water, DMSO, dimethylformamide (DMF), and methanol, respectively, to prepare various dispersions (1 w / v%). Then, 2 mL of each dispersion was put into a plastic cell, and UV-Vis absorption spectrum measurement was performed. The measurement was carried out at a temperature of 25 °C in transmittance mode. The baseline was created by measuring each solvent (about 2 mL) in a plastic cell. The UV-Vis absorption spectra of the various dispersions using the composite materials of Examples 1 and 2 are shown in FIGS. 5(a) and (b), respectively. As can be seen from FIG. 5, the various dispersions showed high transmittance in the visible light region, while the transmittance was 0% in the UVB region. From this, it was confirmed that each composite material of the examples has ultraviolet absorption ability.

[0117] <Dispersion Particle Size> 0.0200 g of each composite material obtained in Examples 1 and 2 was added to 2 mL of DMSO and dispersed to prepare a dispersion (1 w / v%). Then, dynamic light scattering (DLS) measurement was performed on the above DMSO dispersion at 25 °C. The measurement was carried out 3 times at the same solvent and the same concentration with a particle size glass cell (2 mL), a temperature of 25 °C, and an integration number of 25 times. The measuring device used was "ELSZ-2000ZS" manufactured by Otsuka Electronics Co., Ltd. The DLS histograms of the DMSO dispersions of the composite materials of Examples 1 and 2 are shown in FIGS. 6(a) and (b), respectively. As a result, the average dispersion particle size of the composite material of Example 1 was about 10 nm, and that of the composite material of Example 2 was about 11 nm.

[0118] <Redispersibility> Regarding the chloroform dispersion and methanol dispersion prepared in the above organic solvent dispersibility evaluation, precipitation and redispersion of the composite material were repeated. As a result, it was visually confirmed that good dispersibility was shown even after at least 3 operations.

[0119] Example 3 A cast film was formed using the composite material obtained in Example 1. Specifically, polymethyl methacrylate (PMMA) resin and the above composite material were mixed at a specific mass ratio (total amount: 0.2016 g), about 1.5 mL of chloroform was added, and the mixture was stirred at room temperature for 1 hour to dissolve or disperse the PMMA resin and the composite material to obtain a liquid. Next, the above liquid was applied onto a glass substrate and heated in an oven at about 40 °C to distill off the solvent, thereby producing a cast film. Note that cast films with mass ratios of PMMA to the composite material of 75:25, 50:50, and 25:75 were produced respectively. Also, a cast film using only PMMA and a cast film using only the composite material were produced in the same manner respectively. When visually observing the transparency of the five obtained cast films, it was confirmed that all of them were transparent. Photographs of the five cast films are shown in Fig. 7.

[0120] <UV-Vis Absorption Spectrum Measurement> UV-Vis absorption spectrum measurement was performed on the five cast films produced in Example 3. The measurement was carried out at a temperature of 25 °C in transmittance mode. The baseline was created by measuring on a glass substrate with nothing coated. The UV-Vis absorption spectrum is shown in Fig. 8. As can be seen from Fig. 8, each cast film showed a high transmittance in the visible light region, while for the cast films with a composite material ratio of 50 mass% or more, the transmittance was 0% in the UVB region. From this, it was confirmed that the above composite material is useful as an ultraviolet absorber for organic resins.

[0121] <PMMA Degradation Test> Evaluation was carried out on two cast films, namely, a cast film made only of PMMA produced in Example 3 and a cast film with a mass ratio of PMMA to the composite material of 50:50. A high-pressure mercury lamp "HLR100T-2" (main wavelength 365 nm, illuminance 170 mW / cm 2The cast film was irradiated with UV light for 1 hour using a 10 cm irradiation distance. After UV irradiation, the cast film was dissolved in 3 mL of chloroform, and methanol was added to cause reprecipitation. The precipitate (PMMA) was collected by suction filtration while washing with methanol. Gel permeation chromatography (GPC) was performed on PMMA before UV irradiation and the two precipitates (PMMA) collected from each cast film. Specifically, PMMA (0.0010 g) was dissolved in degassed chloroform (eluent: 1.0 mL) to prepare a sample solution (0.1 w / v%). The measurement conditions are as follows. The GPC curves obtained by GPC measurement are shown in Figure 9. In Figure 9, (a) shows the GPC curve of PMMA before UV irradiation, (b) shows the GPC curve of PMMA collected from a cast film consisting of PMMA only after UV irradiation, and (c) shows the GPC curve of PMMA collected from a cast film containing a composite material after UV irradiation. HITACHI L-2490(RI detector),HITACHI L-2130(Pump),Shodex KF-803L,KF805L(Column),Eluent:chloroform,Flow rate:1.0 mL / min,Temperature 40℃,Standard:Polystyrene

[0122] From the results of GPC measurement, the weight average molecular weight (Mw) of PMMA before UV irradiation was 2.45×10 5 The molecular weight distribution (Mw / Mn) of PMMA was 3.82 (Fig. 9(a)), whereas the Mw of PMMA after UV irradiation was 6.11 × 10 4 (Figure 9(b)). The molecular weight was significantly reduced, which suggests that the polymer main chain was severed considerably by UV irradiation. On the other hand, the Mw of PMMA after UV irradiation in the composite material was 2.13 × 10 5 From this, it was found that although there was some decrease in the molecular weight, the decomposition of PMMA could be significantly suppressed (Figure 9(c)).

[0123] Variations of the invention according to the present disclosure are described below. [Appendix 1] A structural unit represented by the following formula (1) [RSiO 3 / 2 ] (1) [In formula (1), R is poly Rio represents a group containing an alkylene chain. and a TiO2 skeleton and has Ti-O-Si bonds. [Additional Note 2] The R is represented by the following formula (1-1): -R 1 -(OR 2 ) n -OR 3 (1-1) [In formula (1-1), R 1 represents a single bond or a linking group, R 2 represents an alkylene group having 2 to 8 carbon atoms; R 3 represents a hydrocarbon group having 1 to 4 carbon atoms (preferably 2 to 6, more preferably 2 to 3), n represents an integer of 2 to 30 (preferably 3 to 20, more preferably 3 to 10, and even more preferably 3 to 5), and the bond extending from the left of the formula is bonded to the silicon atom in formula (1). 2. The titanium-containing composite material according to claim 1, wherein the titanium-containing composite material is a group represented by the formula: [Appendix 3] R 1 is expressed by the following formula (1-2) -R 4 -X- (1-2) [In formula (1-2), R 4 represents a divalent hydrocarbon group (preferably a straight-chain or branched-chain alkylene group having 1 to 18 carbon atoms (more preferably 1 to 10, and even more preferably 2 to 6), or a divalent alicyclic hydrocarbon group), and X represents a carbonyl group or an amide bond (preferably an amide bond). The bond extending from the left in the formula (1-2) is bonded to the silicon atom in the formula (1), and the bond extending from the right is [OR 2 ]. The titanium-containing composite material according to claim 2, wherein the linking group is represented by the following formula: [Appendix 4] The titanium-containing composite material according to any one of Appendices 1 to 3, comprising a core portion which is titanium oxide containing the TiO2 skeleton, and a shell portion which is formed so as to cover the core portion and is made of polysilsesquioxane containing a constitutional unit represented by formula (1). [Appendix 5] The titanium-containing composite material according to any one of Appendices 1 to 4, wherein the coordination number of oxygen atoms to one titanium atom in the TiO2 framework is 1 or more selected from the group consisting of 2, 3, 4, 6, and 8 (preferably including 6). [Appendix 6] The titanium-containing composite material according to any one of Appendices 1 to 5, wherein when dispersed in dimethyl sulfoxide, the average particle size of the composite material in dimethyl sulfoxide is 100 nm or less (preferably 50 nm or less, more preferably 20 nm or less). [Appendix 7] The titanium-containing composite material according to any one of Appendices 1 to 6, wherein the atomic ratio of silicon atoms to titanium atoms (latter / former) is 0.05 to 1.0 (preferably 0.1 to 0.8, more preferably 0.3 to 0.6). [Appendix 8] The titanium-containing composite material according to any one of Appendices 1 to 7, wherein the proportion of the constitutional units represented by the formula (1) relative to 100 mass% of the total amount of all siloxane constitutional units in the composite material is 50 mass% or more (preferably 70 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more). [Appendix 9] The titanium-containing composite material according to any one of Appendices 1 to 8, wherein the total proportion of the polysilsesquioxane containing the constitutional unit represented by the formula (1) and the TiO2 structure in the composite material is 50 mass% or more (preferably 70 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more) relative to 100 mass% of the total amount of the composite material. [Appendix 10] The titanium-containing composite material according to any one of Appendices 1 to 9, which is amorphous. [Appendix 11] An ultraviolet absorber using the titanium-containing composite material according to any one of Appendices 1 to 10.

[0124] [Appendix 12] A method for producing a titanium-containing composite material according to any one of Appendices 1 to 10, comprising a hydrolysis / condensation step of reacting a compound represented by the following formula (A) with a compound represented by the following formula (B) in the presence of water and an acid catalyst to hydrolyze and condense them: RSi(OR a )3(A) [In formula (A), R represents a group containing a polyoxyalkylene chain, R a represents a hydrocarbon group having 1 to 4 carbon atoms. Ti(OR b )4(B) [In formula (B), R b represents a hydrocarbon group having 1 to 6 carbon atoms. [Appendix 13] The method for producing a titanium-containing composite material according to appendix 12, wherein the hydrolysis / condensation step comprises a condensation stage in which the compound represented by formula (A) and the compound represented by formula (B) are reacted and condensed in the presence of the acid catalyst in a system to which no water is added, and a hydrolysis / condensation stage in which water is added after the condensation stage to hydrolyze and condense in the presence of water. [Appendix 14] The method for producing a titanium-containing composite material according to Appendices 13, wherein the acid catalyst contains an acidic alcohol. [Appendix 15] The method for producing a titanium-containing composite material according to any one of Appendices 12 to 14, wherein the hydrolysis and condensation step is carried out by a sol-gel method. [Additional Note 16] The R is represented by the following formula (1-1): -R 1 -(OR 2 ) n -OR 3 (1-1) [In formula (1-1), R 1 represents a single bond or a linking group, R 2 represents an alkylene group having 2 to 8 carbon atoms; R 3 represents a hydrocarbon group having 1 to 4 carbon atoms (preferably 2 to 6, more preferably 2 to 3), n represents an integer of 2 to 30 (preferably 3 to 20, more preferably 3 to 10, and even more preferably 3 to 5), and the bond extending from the left of the formula is bonded to the silicon atom in formula (1). 16. The method for producing a titanium-containing composite material according to any one of claims 12 to 15, wherein R is a group represented by the following formula: [Appendix 17] R 1 is expressed by the following formula (1-2) -R 4 -X- (1-2) [In formula (1-2), R 4represents a divalent hydrocarbon group (preferably a straight-chain or branched-chain alkylene group having 1 to 18 carbon atoms (more preferably 1 to 10, and even more preferably 2 to 6), or a divalent alicyclic hydrocarbon group), and X represents a carbonyl group or an amide bond (preferably an amide bond). The bond extending from the left in the formula (1-2) is bonded to the silicon atom in the formula (1), and the bond extending from the right is [OR 2 ]. The method for producing a titanium-containing composite material according to claim 16, wherein the linking group is represented by the following formula: [Explanation of symbols]

[0125] 1 Composite materials 2 Core 3. Shell 31 Polysilsesquioxane skeleton 32 Polyoxyalkylene chain-containing group

Claims

1. A constitutional unit represented by the following formula (1): [RSiO 3/2 ] (1) [In formula (1), R is a group represented by the following formula (1-1). -R 1 -(OR 2 ) n -OR 3 (1-1) [In formula (1-1), R 1 represents a single bond or a linking group, R 2 represents an alkylene group having 2 to 8 carbon atoms, R 3 represents a hydrocarbon group having 1 to 4 carbon atoms, n represents an integer of 2 to 30, and the bond extending from the left of the formula is bonded to the silicon atom in formula (1). The linking group is at least one selected from the group consisting of a divalent hydrocarbon group, a urethane bond, a carbonyl group, an ether bond, an ester bond, a carbonate bond, an amide bond, and a group in which one or more of these groups are linked together. and TiO 2 A skeleton having a Ti—O—Si bond, The polysilsesquioxane skeleton includes a structural unit represented by the formula (1), The titanium-containing composite material comprises a core-shell structure having a core portion made of the TiO 2 skeleton and a shell portion made of polysilsesquioxane containing a constitutional unit represented by formula (1).

2. 2. The titanium-containing composite material according to claim 1, wherein when dispersed in dimethyl sulfoxide, the average particle size of the composite material in dimethyl sulfoxide is 100 nm or less.

3. 3. The titanium-containing composite material according to claim 1, wherein the atomic ratio of silicon atoms to titanium atoms (latter / former) is 0.05 to 1.

0.

4. 4. A method for producing a titanium-containing composite material according to claim 1, comprising a hydrolysis / condensation step of reacting a compound represented by the following formula (A) with a compound represented by the following formula (B) in the presence of water and an acid catalyst to hydrolyze and condense the compound: RSi(OR a ) 3 (A) [In formula (A), R represents a group containing a polyoxyalkylene chain, R a represents a hydrocarbon group having 1 to 4 carbon atoms. Ti(OR b ) 4 (B) [In formula (B), R b represents a hydrocarbon group having 1 to 6 carbon atoms.

5. 5. The method for producing a titanium-containing composite material according to claim 4, wherein the hydrolysis and condensation process comprises a condensation stage in which the compound represented by formula (A) and the compound represented by formula (B) are reacted and condensed in the presence of the acid catalyst in a system to which no water is added, and a hydrolysis and condensation stage in which water is added after the condensation stage to hydrolyze and condense in the presence of water.

6. The method for producing a titanium-containing composite material according to claim 5, wherein the acid catalyst comprises an acidic alcohol.

7. The method for producing a titanium-containing composite material according to any one of claims 4 to 6, wherein the hydrolysis and condensation step is carried out by a sol-gel method.

Citation Information

Patent Citations

  • Silsesquioxane-titania hybrid polymer

    JP2009513788A

  • Water-soluble composite material containing titanium oxide, and manufacturing method thereof

    JP2010209288A

  • Synthesis, cap formation, and dispersion of nanocrystals

    JP2013534459A

  • Polymer composition, polymer composite and optical film

    JP2018150530A

  • Transfer film, and in-mold molded article

    JP2018192704A